Education and globalization processes - V. S. Senashenko (Высшее образование в России)
The article is devoted to some possible consequences for higher education system after Russia’s entering World Trade Organization. In particular the author discusses the problems and difficulties concerning formation of the educational programs. The mechanisms minimizingthese difficulties are considered.